Cardiovascular Disease in Japanese Patients with Type 2 Diabetes Mellitus - Fujihara, Kazuya (Ann Vasc Dis, 2018)
Individuals with diabetes have a two- to four-fold increased risk of coronary artery disease (CAD) and higher mortality rates than those without diabetes. Because not only microvascular but also macrovascular disease in patients with diabetes are known to predispose patients to a lower quality of life as well as lead to higher mortality rates, identifying and managing risk factors of CAD is of clinical relevance in diabetes care. A number of antihyperglycemic drugs are currently approved for the treatment of hyperglycemia in patients with type 2 diabetes mellitus (T2DM), with several new drugs having been developed during the last decade. Diabetes-related complications have been substantially reduced worldwide. However, in view of the current situation in which both the prevalence of obesity and glucose abnormality have increased worldwide, including Japan, diet and exercise remain the crucial means of treatment for patients with diabetes. Furthermore, predicting the development of CAD is essential. This review summarizes data from recent studies on cardiovascular disease in patients with T2DM, focusing on clinical trials and big data, including studies involving Japanese individuals.